2007
DOI: 10.1037/0033-3204.44.4.384
|View full text |Cite
|
Sign up to set email alerts
|

Big ideas for psychotherapy training.

Abstract: Research indicates that traditional psychotherapy training practices are ineffective in durably improving the effectiveness of psychotherapists. In addition, the quantity and quality of psychotherapy training research has also been limited in several ways. Thus, based on extant scholarship and personal experience, we offer several suggestions for improving on this state of affairs. Specifically, we propose that future psychotherapy trainings focus on a few "big ideas," target psychotherapist meta-cognitive ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 54 publications
(53 reference statements)
2
48
1
Order By: Relevance
“…To this end we argue that there is converging evidence to suggest that therapeutic training should emphasize the person of the therapist (Duncan, 2010;Fauth, Gates, Vinca, Boles, & Hayes, 2007;Geller & Greenberg, 2012) and enhance the development of empathic communication skills, the capacity to enhance clients' emotional expression and self-regulation, and the capacity to develop a secure and productive therapeutic alliance for the facilitation of client narrative disclosure and productive meaning-making in therapy sessions.…”
Section: Implications For Hpr Practice and Trainingmentioning
confidence: 97%
“…To this end we argue that there is converging evidence to suggest that therapeutic training should emphasize the person of the therapist (Duncan, 2010;Fauth, Gates, Vinca, Boles, & Hayes, 2007;Geller & Greenberg, 2012) and enhance the development of empathic communication skills, the capacity to enhance clients' emotional expression and self-regulation, and the capacity to develop a secure and productive therapeutic alliance for the facilitation of client narrative disclosure and productive meaning-making in therapy sessions.…”
Section: Implications For Hpr Practice and Trainingmentioning
confidence: 97%
“…Even so, this understanding of the training process has been largely taken for granted by some, and overlooked by others. If, as most trainers seem to agree, personal development is an important component to a therapist's professional growth (Fauth et al, 2007;Geller et al, 2005), then research is needed to elaborate the types of personal, interpersonal, and reflexive changes that trainees undergo as a critical, albeit largely undeclared, product of psychotherapist training. The current study examines graduate students in a skills-based course on experiential-integrative psychotherapy.…”
Section: Psychotherapy Training As An Exercise In Personal Developmentmentioning
confidence: 97%
“…Still, little research has empirically demonstrated or substantively described these ''other goals.'' Ideally, training cultivates one's personal and relational qualities, such as emotional maturity, empathic attunement, and the ability to internally manage one's own difficulties during an interpersonal encounter (Fauth, Gates, Vinca, & Boles, 2007). In this sense, therapist training can act as a sort of ''therapy'' in and of itself, insofar as it offers an exercise of self-development in the personal qualities required to be an effective therapist (Pascual-Leone, 2012).…”
Section: Psychotherapy Training As An Exercise In Personal Developmentmentioning
confidence: 98%
“…Counsellor and psychotherapy training has attracted little attention to date (Fauth et al, 2007), and literature written on integrative training tends to focus upon idealised training programmes (e.g. Castonguay, 2000;Norcross & Beutler, 2000).…”
Section: Research On Integrative Trainingmentioning
confidence: 99%